2022
DOI: 10.4082/kjfm.21.0015
|View full text |Cite
|
Sign up to set email alerts
|

Is Ankle Kinesio Taping Effective to Immediately Change Balance, Range of Motion, and Muscle Strength in Healthy Individuals? A Randomized, Sham-Controlled Trial

Abstract: Background: The ankle–foot complex plays a key role in maintaining balance because it collects proprioceptive data. Kinesio taping (KT) is a rehabilitative method performed by the cutaneous application of a special elastic tape. The mechanical correction technique of KT was suggested to reposition the joints and alter balance parameters. The aim was to reveal the pure effects of ankle KT on balance, range of motion (ROM), and muscle strength in healthy individuals.Methods: Forty healthy students were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In a previous study that has reported an increase in ankle dorsiflexion ROM, a Y-shaped elastic tape was applied from the navicular tuberosity of the plantar to the medial and lateral heads of the gastrocnemius muscle 12 ) . On the other hand, in previous studies that reported no change, elastic tape was not applied to the gastrocnemius but around the ankle joint 13 , 14 ) . DFA of the participants in present study did not increase, which may be owing to the difference in the area of tape application compared to that in previous studies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a previous study that has reported an increase in ankle dorsiflexion ROM, a Y-shaped elastic tape was applied from the navicular tuberosity of the plantar to the medial and lateral heads of the gastrocnemius muscle 12 ) . On the other hand, in previous studies that reported no change, elastic tape was not applied to the gastrocnemius but around the ankle joint 13 , 14 ) . DFA of the participants in present study did not increase, which may be owing to the difference in the area of tape application compared to that in previous studies.…”
Section: Discussionmentioning
confidence: 95%
“…Several previous studies have reported on the effectiveness of elastic tape application for ankle dorsiflexion ROM in healthy individuals, with conflicting results. Although one study has identified a significant increase in ankle dorsiflexion ROM 12) , two other studies have reported no change 13,14) . Therefore, the efficacy of elastic tape application for ankle dorsiflexion ROM is uncertain.…”
Section: Discussionmentioning
confidence: 98%